Mathematical aspects of network routing optimization - Oliveira, Carlos A. S. (Springer optimization and its applications, 2011)
Mathematical Aspects of Network Routing Optimization provides a thorough introduction to the subject of algorithms for network routing and focuses on multicast and wireless ad hoc systems. The modern world is connected through large-scale, computational networked systems such as the Internet and because of the ever-advancing technology of networking, efficient algorithms have become increasingly necessary to solve some of the problems developing in this area. This work focuses on computational issues arising from the process of optimizing network routes, such as the quality of resulting links and their reliability. Algorithms are key to understanding the protocols underlying multicast routing. The main objective in the text is to derive efficient algorithms, with or without the guarantee of approximation, that can be applied to address these problems. Notes have been provided for basic topics such as graph theory and linear programming to assist those who are not fully acquainted with the mathematical topics presented throughout the book. This book is designed for graduate students, researchers, and professionals interested in understanding the algorithmic and mathematical ideas behind routing in computer networks and network algorithms